The Effect of 10 Most Common Nonurological Primary Cancers on Survival in Men With Secondary Prostate Cancer - Wenzel, Mike; Nocera, Luigi; Würnschimmel, Christoph; Collà Ruvolo, Claudia; Tian, Zhe; Saad, Fred; Briganti, Alberto; Tilki, Derya; Graefen, Markus; Becker, Andreas; Roos, Frederik C.; Chun, Felix K. H.; et al. (Frontiers in Oncology, 2021)
Background: To test the effect of the ten most common non-urological primary cancers (skin, rectal, colon, lymphoma, leukemia, pancreas, stomach, esophagus, liver, lung) on overall mortality (OM) after secondary prostate cancer (PCa). Material and Methods: Within the Surveillance, Epidemiology and End Results (SEER) database, patients with ten most common primary cancers and concomitant secondary PCa (diagnosed 2004-2016) were identified and were matched in 1:4 fashion (age, year at diagnosis, race/ethnicity, treatment type, TNM-stage) with primary PCa controls. OM was compared between secondary and primary PCa patients and was stratified according to primary cancer type, as well as according to time interval between primary cancer vs. secondary PCa diagnoses. Results: We identified 24,848 secondary PCa patients (skin, n=3,871; rectal, n=798; colon, n=3,665; lymphoma, n=2,583; leukemia, n=1,102; pancreatic, n=118; stomach, n=361; esophagus, n=219; liver, n=160; lung, n=1,328) vs. 531,732 primary PCa patients. Secondary PCa characteristics were less favorable than those of primary PCa patients (PSA and grade) and smaller proportions of secondary PCa patients received active treatment. After 1:4 matching, all secondary PCa exhibited worse OM than primary PCa patients. Finally, subgroup analyses showed that the survival disadvantage of secondary PCa patients decreased with longer time interval since primary cancer diagnosis and subsequent secondary PCa. Conclusion: Patients with secondary PCa are diagnosed with less favorable PSA and grade. Even after matching for PCa characteristics, secondary PCa patients still exhibit worse survival. However, the survival disadvantage is attenuated, when secondary PCa diagnosis is made after longer time interval, since primary cancer diagnosis.